The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1186/1742-4755-4-10
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of midline versus medio-lateral episiotomy

Abstract: Background: Episiotomy is the surgical enlargement of the vaginal orifice by an incision of the perineum during the second stage of labor or just before delivery of the baby. During the 1970s, it was common to perform an episiotomy for almost all women having their first delivery, ostensibly for prevention of severe perineum tears and easier subsequent repair. However, there are no data available to indicate if an episiotomy should be midline or medio-lateral. We compared midline versus medio-lateral episiotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
1
20
0
2
Order By: Relevance
“…Our finding suggests that an increased use of episiotomy among HIV positive women with imminent tear may have reduced the rate of perineal tears in this group. Episiotomies are easier to repair as opposed to perineal tears African Journal of Reproductive Health December 2017; 21 (4): 71 which may also extend to involve the anal sphincter and rectum making repair more difficult 16 . However, no patient in the study had third or fourth perineal tears.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding suggests that an increased use of episiotomy among HIV positive women with imminent tear may have reduced the rate of perineal tears in this group. Episiotomies are easier to repair as opposed to perineal tears African Journal of Reproductive Health December 2017; 21 (4): 71 which may also extend to involve the anal sphincter and rectum making repair more difficult 16 . However, no patient in the study had third or fourth perineal tears.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that episiotomies angled too close to the midline are at higher risk of causing OASI. The incidence of OASI in units that practise midline episiotomies is 7-20 % [19,64,71,72]. In a quasirandomised trial, Coats et al [73] found that 24 % of midline episiotomies in primiparous women were associated with OASIs in contrast to 2 % of mediolateral episiotomies.…”
Section: Angle Of the Episiotomymentioning
confidence: 99%
“…Several studies have compared episiotomies to an intact perineum or to spontaneous second degree lacerations in relation to pain perception (60,71,94,109), but very few studies have compared different episiotomy techniques (21,110,111). Prior to Paper I, no study had previously included the lateral technique in a comparative study.…”
Section: Perineal Painmentioning
confidence: 99%